The machinations of change: Beepeearr, debunking and the `In-Between' - Collins, David (2004)
This article examines recent developments in management knowledge in an attempt to rethink the everyday strategies, practices and processes that make change in organizations. Focussing on business process re-engineering (BPR), it offers a critical analysis of the production and consumption of management knowledge which seeks an engagement with the experiences of practitionefrs. Employing a Latourian account of the making of ideas and of the `hybrids' of nature and culture, the article explores the limitations of both BPR and those critiques that would debunk it as so much faddish nonsense. The article concludes by suggesting five ways in which this Latourian account of the making of change alters our appreciation of the ways and means of guru theorizing in general and the modus operandi of BPR in particular. - Reproduced.
Keywords: Management; Organizational change